Benzimidazole functionalization enables efficient multi-resonance TADF with accelerated spin-flipping and balanced charge transport - Ji-Hua Tan; Si-Wei Chen; Xin-Lu Li; Han-Nan Shi; Xiao-Long Liu; Yao-Zu Su; Xiaofeng Wang; Jun-Hua Zhuang; Chengxiang Shi; Jia-Ming Jin; Shaoyun Yin; Jia-Xiong Chen; et al. (Chemical Engineering Journal, 2026)

Intelligent identification of GPR road internal voids based on stochastic media augmentation and optimized gradient boosting - Liqi Chen; Hongya Yue; Chuanyi Ma; Zhuhao Zhang; Zhijie Li; Wenyang Han; Peizhi Zhuang (Transportation Geotechnics, 2026)

Alcohol and high-fat diet aggravate colitis-induced liver injury via glucocorticoid/IL-6-SAA1 axis in mice - Mingrui Zhao; Han Li; Xinghua Gao; Huijuan Da; Xun Cui; Dongquan Jing; Qixiang Zhao; Ying Wang; Yanling Guo; Zhenhua Gao; Shentian Zhuang; Qiuhua Cao (Food and Chemical Toxicology, 2026)

Urban greening as a potential nature-based solution for heat-related health burden: Evidence from acute myocardial infarction in a megacity - Yuansong Zhuang; Zhen He; Dongyang Pan; Yakun Zhao; Yuxiong Chen; Yitao Han; Siqi Tang; Chenglin Li; Jinyan Lei; Otthein Herzog; Zhiqiang Wu; Zhongjie Fan (Sustainable Cities and Society, 2026)

High-fidelity phase-change transfer platform for laser-induced graphene toward multifunctional flexible electronics - Zhao Li; Yanping Song; Wenjie Shao; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Zhuang Miao; Shudong Zhang; Cui Liu; Min Xi; et al. (Chemical Engineering Journal, 2026)

Paradigm shifts in achieving global food security: toward a resilient and sustainable future - Shaokun Li; Jialu Xu; Huaqing Wu; Jichong Han; Huimin Zhuang; Zongliang Zhang; Xinyu Wu; Zhao Zhang (Food Security, 2026)

Chemical speciation and release characteristics in different environments of heavy metals in thermally activated red mud - Jing Yang; Xin Fan; Hailan Zhang; Xirong Niu; Xiaobin Han; Zhuang Zhang; Xinke Li; Yuanqi Zhang; Wenzhen Wu; Hailong Cao (Journal of Hazardous Materials, 2026)

A practical framework for evaluating phosphorus redistribution after dewatering in tailings dry disposal - Jikang Han; Changlong Zheng; Fengjiu Li; Zhuang Li; Yuhui Wang (Journal of Cleaner Production, 2026)

Systematic evaluation reveals the dynamics and functions of horizontal gene transfer widespread in algae - Limin Jia; Liangwei Li; Qijin Ge; Yanchun You; Kai Han; Sibo Wang; Jianwei Chen; Dazhi Wang; Xin Liu; Yunyun Zhuang; Guangyi Fan; Chengcheng Shi (Marine Life Science & Technology, 2026)

Impact of polystyrene nanoplastics on soil microbial biomass - Chunyang Li; Heping Shang; Zeyu Cai; Weili Jia; Yini Cao; Xiupei Zhou; Jie Zhang; Sixiang Zhuang; Ziqin Lin; Anqi Liang; Lanfang Han; Jason C. White; et al. (Environmental Chemistry Letters, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Divergent edaphic filters drive ecosystem-specific microbiome assembly and metabolic strategies in Northern China's transitional zone - Zhaojuan Zhang; Songning Guo; Xin Li; Zifei Wang; Xiao Han; Jiaxin Li; Zhuang Li; Jing Zhao; Steven L. Stephenson; V.I. Gmoshinskiy; A.V. Kurakov; Yu Li; et al. (Environmental Research, 2026)

Precise mapping of high-temperature adult-plant stripe rust resistance gene Yr52 in wheat - Mingjie Xiang; Yibo Zhang; Shuaiwei Cao; Jiangna Han; Haohao Yan; Chenfang Wu; Jiale Li; Xunying Yuan; Xiangrui Cheng; Shuqing Yang; Zhuang Li; Xiaoting Wang; et al. (Theoretical and Applied Genetics, 2026)

Development and Evaluation of a Novel 3D Variational Assimilation Framework for Regional Chemistry–Weather Forecasting - Zhaorong Zhuang; Weihong Tian; Liping Huang; Xueshun Shen; Wei Han; Hong Wang; Xingliang Li; Xiaoye Zhang (Journal of Meteorological Research, 2026)

Boundary-controlled prediction of the Sauter mean bubble diameter in three-phase fluidized bed flotation columns - Jikang Han; Changlong Zheng; Zhuang Li; Peng Chen; Yuhui Wang; Yanfeng Li (Chemical Engineering Journal, 2026)

Yearly-scale deep crustal fluid transfer implied by gravity changes from in-situ observations around the 2021 Yangbi M6.4 earthquake, China - Linhai Wang; Shi Chen; Jiancang Zhuang; Yue Liu; Lulu Jia; Jiancheng Han; Bei Zhang; Yongbo Li (Tectonophysics, 2026)

Impact of air pollutants on PDGFs mRNA in platelets and association of PDGFs mRNA expression level with acute myocardial infarction and major adverse cardiovascular events - Jichao Xie; Hankun Xie; Liang Xu; Fangyuan Liu; Qian Zhuang; Xianghai Zhao; Junxiang Sun; Pengfei Wei; Yunjie Yin; Yanchun Chen; Feifan Wang; Xu Han; et al. (Journal of Hazardous Materials, 2026)

Trade-off-free intrinsically stretchable electroluminescent films enabled by a thermally activated delayed fluorescence plasticizer - Wenzhong Bian; Xinxin Ban; Junyi Chen; Mengting Li; Caixia Yang; Hongyu Zhuang; Shuang Chen; Jiangqi Jiang; Wenli Shi; Hai Zhou; Youqiang Qian; Zhaoxiang Han; et al. (Chemical Engineering Journal, 2026)

Zinc intoxication triggers ferroptosis in Cryptocaryon irritans tomonts through mitochondrial damage and lipid peroxidation - Zhi Luo; Baotun Wang; Jingyu Zhuang; Hebing Wang; Zhicheng Li; Jizhen Cao; Qin Han; Chuanfu Dong; Anxing Li (Aquaculture, 2026)

AID/APOBEC-like cytidine deaminases are important mediators of VLR-based adaptive immunity in lampreys - Zihao Yan; Jingjing Lu; Yuesi Zhou; Liang Zhao; Ding Li; Huining Jia; Ayqeqan Nurmamat; Min Xiu; Shuyuan Zhang; Ruyu Zhuang; Ya Pang; Tiesong Li; et al. (Fish & Shellfish Immunology, 2026)

Mechanisms, treatment strategies and predictive biomarkers of drug resistance in acute myeloid leukemia - Jianjian Zhuang; Yue Li; Yingqiong Zhang; Yiling Huang; Yijia Han; Nengming Lin; Yangling Li (Mutation Research - Reviews in Mutation Research, 2026)

Membrane separation coupled with electrochemical process for degradation of high-concentration coking wastewater - Fei Han; Chang Liu; Yuankang Yue; Weijie Song; Yifan Li; Mingyao Zhao; Xiaojie Zhuang (Journal of Water Process Engineering, 2026)

Corrigendum to “Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells” [Vet. Microbiol. 310 (2025) 110723] - Kui Xu; Yu-Ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Synergistic thermal activation of eggshell powder and low-calcium red mud for red mud-based all solid waste cementitious materials - Xin Fan; Xirong Niu; Hailan Zhang; Jing Yang; Zhuang Zhang; Xiaobin Han; Lepeng Tian; Shenguang Liu; Yuanqi Zhang; Peijun Li (Chemical Engineering Journal, 2025)

Gut Microbiota Improve the Prediction of Stroke-Associated Pneumonia Risk and Outcomes in Acute Ischemic Stroke - Yi-si Lin; Jia-hao Chen; Wei-hao Zhuang; Jia-ni Huang; Yi-han Chen; Jie Zhang; Jia Li; Meng Huang; Jia-long Hou; Shuang-jie Qian; Zhi-bo Chen; Yan-lei Zhang; et al. (Translational Stroke Research, 2025)

Uncovering the gut microbiome and antibiotic resistome of mammals on the Tibetan Plateau - Chen Tian; Zecheng Tang; Xiaoyu Zhang; Xueqin Yao; Yitian Li; Daohua Zhuang; Yu Luo; Teng Li; Liyan Bai; Fangfang Zhao; Lei Zhu; Guolin Shi; et al. (Science China Life Sciences, 2025)

Exploring the evolutionary conservation and functional implications of Endothelin Converting Enzyme 1 (ECE1) in lamprey (Lethenteron reissneri) - Shuyuan Zhang; Zihao Yan; Ayqeqan Nurmamat; Ruyu Zhuang; Yuesi Zhou; Min Xiu; Ya Pang; Ding Li; Liang Zhao; Xin Liu; Yinglun Han (Fish Physiology and Biochemistry, 2025)

Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells - Kui Xu; Yu-ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Botulinum Toxin A (BTA) for pain and function improvement in osteoarthritis: a systematic review and meta-analysis of clinical efficacy evidence from randomized controlled trials - Beibei Lei; Weisheng Zhuang; Yage Wang; Shenhong Ma; Heling Wang; Di Zhang; Qiaohua Han; Xu Wang; Qixin Ding; Yuefang Li (Toxicon, 2025)

Weak-prior medical image matting based on microscale-searching evolutionary optimization - Li Kang; Han Huang; Yihui Liang; Baoxiong Zhuang (Swarm and Evolutionary Computation, 2025)

Environmental impacts of concentrated apple juice supply chain based on the major apple producing regions in China - Zhiyao Chang; Wenxue Li; Minghao Zhuang; Mingzhao Han; Yu Peng; Mo Li; Yuanying Ni; Xin Wen (Science of The Total Environment, 2025)

Glycerol treatment enhances resistance to soft rot disease and maintains postharvest quality in kiwifruit - Han Wang; Xumeng Zhang; Kunyan Li; Mengbo Wu; Qiguo Zhuang; Mingzhang Li; Pedro Garcia-Caparros; Yue Xie; Cheng Hu; Mingchun Liu (Postharvest Biology and Technology, 2025)

Kinetics and mechanism of iron leaching from scrap copper smelting slag flotation tailings by hydrochloric acid - Fei Han; Yifan Li; Xiaojie Zhuang; Mingyao Zhao; Weijie Song; Yinhua Wan (Journal of Environmental Chemical Engineering, 2025)

The Systematic Study on the Effects of Adding Bile Acids and Zinc to Laying Hens’ Diets: From Production Performance to Egg Quality, Trace Element Content, and Intestinal Microorganisms - Shou Kang Cao; Yi Fan Li; Han Chen; Yu Qing Mu; Xue Zhuang Wu (Biological Trace Element Research, 2025)

Prediction of indoor multi-physical fields using dimension reduction graph neural networks - Hu Gao; Lei Zhuang; Chenxi Li; Xu Han; Hua Zhang; Jing Liu (Building and Environment, 2025)

Linking rhizosphere bacterial life-history strategies with wheat growth under drought stress - Yanshuo Pan; Binhui Liu; Shan Zhuang; Hongzhe Wang; Yanjie Qi; Jieyin Chen; Didier Lesueur; Liang Xiao; Yuzhong Li; Dongfei Han (Soil Ecology Letters, 2025)

Immunotoxic effect and mechanisms of Fusarium mycotoxins on human immune cells: A focus on T cells and macrophages - Jing Yang; Xiaohong Wang; Qiannan Zhang; Hongyang Cui; Lijuan You; Zhisen Zhuang; Yaru Tian; Xiaomin Han; Miaoying Shi; Li Bai; Xudong Jia; Hui Yang (Toxicology, 2025)

Machine learning based prediction by PlantCdMiner and experimental validation of cadmium-responsive genes in plants - Chaoqun Xu; Ling Sun; Lu-Dan Zhang; Ze-Jun Guo; Ji-Cheng Wang; Li-Han Zhuang; Dong-Na Ma; Ling-Yu Song; Jing Li; Qian-Su Ding; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2025)

Oxidative stress, inflammation, and apoptosis contribute to the pathogenesis of Amyloodinium ocellatum infection in yellowfin seabream (Acanthopagrus latus) - Zhicheng Li; Jingyu Zhuang; Hebing Wang; Jizhen Cao; Baotun Wang; Qing Han; Zhi Luo; Chuanfu Dong; Anxing Li (Fish & Shellfish Immunology, 2025)

Cascade-responsive nanoplatform for synergistic cancer therapy via ROS amplification and hypoxia targeting - Chunyun Xu; Yanfang Ding; Jingjing Qi; Peng Chu; Hongjie Huo; Zhuang Wang; Qingxuan Han; Yuan Liang; Ning Yang; Youwei Xu; Ligeng Xu; Lixue Chen; et al. (Chemical Engineering Journal, 2025)

Significant contribution of seawater infiltration and hydrothermal activity on lithium enrichment in the Ceshui Formation coal of the LianShao Coalfield, Hunan Province, South China - Jing Li; Yuan Wang; Han Zhang; Amina Wumaier; Xinguo Zhuang; Xavier Querol; Natalia Moreno; Baoqing Li (Frontiers in Marine Science, 2025)
The Ceshui Formation is one of the most important coal-bearing formation of the Lower Carboniferous in China, especially in South China. This study investigates the mineralogical and geochemical characteristics of the Lower Carboniferous Ceshui Formation coal from the studied area, Lianshao Coalfield, Hunan Province, with special emphasis on significant lithium enrichment in the studied area. The Ceshui Formation bituminous from the Toushi open-pit mine is characterized by medium-low ash yield, low volatile matter yield and low sulfur content. Minerals occurring in the coal are mainly composed of kaolinite, tobelite and calcite, followed by quartz, anatase, ankerite, microcline, siderite and illite, with a trace amount of pyrite. Compared with the average values in worldwide coals, Li is significantly enriched in the Ceshui Formation coals in the studied area, occurring mainly in kaolinite and secondarily in chlorite. The closer to the roof and floor, the higher the concentration of Li. The concentration of Li 2 O in coal ashes exceeds the Extraction Standard for Li 2 O in coal-bearing strata, presenting a promising metallogenic potential. The enrichment of Li in the Toushi coals is primarily derived from the supply of terrigenous sediment provenance and strongly influenced by its interaction with infiltrated seawater and hydrothermal fluids. The sediment provenance of the terrigenous clastic was derived from the Li-rich granite in the Xuefeng Oldland to the northeast of Lianshao coalfield. The Ceshui Formation coal in the studied area was formed in a marine-influenced transitional sedimentary environment, and Li from Li-rich granitic debris was more readily enriched in coal seams during slow sea regressive process. The infiltration of hydrothermal fluids and interaction with Li-bearing terrestrial material further promoted Li enrichment in the Toushi coals.

Enrichment of Al-Li-Ga-Nb(Ta)-Zr(Hf) in the Permo-Carboniferous coal-bearing sequences of the Jungar Coalfield, northern China - Yuan Wang; Jing Li; Daohua Wang; Xin Luo; Wei Yuan; Hongguang Cai; Han Zhang; Xiangdong Feng; Shuai Guo; Wenhua Li; Xinguo Zhuang; Van Long Hoang (International Journal of Coal Geology, 2025)

The accessory secretion system in Streptococcus agalactiae regulates protein secretion, stress resistance, adhesion, immune evasion, and virulence - Jizhen Cao; Han Li; Qing Han; Zhicheng Li; Jingyu Zhuang; Chuanfu Dong; Anxing Li (Fish & Shellfish Immunology, 2025)

Tidal-driven N2O emission is a stronger resister than CH4 to offset annual carbon sequestration in mangrove ecosystems - Chunwei Fu; Zhibo Shen; Shiheng Tang; Fengying Li; Xin Quan; Yang Wang; Ya Zhuang; Jiasen Zhong; Jianan Liu; Jianzhong Su; Min Xu; Yu Han; et al. (Science of The Total Environment, 2025)

Food consumption away from home had divergent impacts on diet nutrition quality across urban and rural China - Huaqing Wu; Zhao Zhang; Jialu Xu; Jie Song; Jichong Han; Jing Zhang; Qinghang Mei; Fei Cheng; Huimin Zhuang; Shaokun Li (Food Security, 2025)

Space weathering characteristics of lunar permanently shadowed regions soils: Evidence from experimental simulation - Zixuan Han; Yang Li; Chen Li; Ronghua Pang; Sizhe Zhao; Zhuang Guo; Kairui Tai; Rui Li; Zhenhao Hu; Li Liu (Acta Geochimica, 2025)

A quantitative real-time PCR assay for rapid detection and quantification of Amyloodinium ocellatum parasites in seawater samples - Jingyu Zhuang; Zhicheng Li; Jizhen Cao; Zhi Luo; Baotun Wang; Qing Han; Hebing Wang; Han Li; Chenxi Wang; Chuanfu Dong; Anxing Li (Aquaculture, 2025)

The effect of varying dissolved oxygen levels on Cryptocaryoniasis in cage-farmed Larimichthys crocea - Baotun Wang; Qingkai Guo; Zhi Luo; Jingyu Zhuang; Chenxi Wang; Zhicheng Li; Han Li; Qing Han; Jizhen Cao; Hebing Wang; Anxing Li (Aquaculture, 2025)

A tetrahedral DNA nanoplatform with ultrasound-triggered biomimetic nanocarriers for targeted siMCM2 delivery and reversal of imatinib resistance in gastrointestinal stromal tumors - Li Han; Quan Dai; Chuanshi He; Jinshun Xu; Likun Cui; Xiaoxiao Xie; Zijian Zhang; Min Zhuang; Xiangyu Li; Man Lu (Chemical Engineering Journal, 2025)

An improved process for the preparation of Si-Fe-Al-Ca alloy from coal gasification fine slag via three-phase plasma smelting - Yaoxuan Wang; Haiyu Li; Zhaoyang Zhang; Xiaolin Guo; Hongbing Du; Wang Han; Yanxin Zhuang; Pengfei Xing (Process Safety and Environmental Protection, 2024)

Vacuum-thermal alteration of lunar soil: Evidence from iron whiskers on troilite in Chang’e-5 samples - Chen Li; Yang Li; Kuixian Wei; Xiumin Chen; Kairui Tai; Zhuang Guo; Rui Li; Han Yu; Xiongyao Li; Wenhui Ma; Jianzhong Liu (Geochimica et Cosmochimica Acta, 2024)

Stagnating rice yields in China need to be overcome by cultivars and management improvements - Huimin Zhuang; Zhao Zhang; Jichong Han; Fei Cheng; Shaokun Li; Huaqing Wu; Qinghang Mei; Jie Song; Xinyu Wu; Zongliang Zhang; Jialu Xu (Agricultural Systems, 2024)

A detailed analysis of 16S rRNA gene sequencing and conventional PCR-based testing for the diagnosis of bacterial pathogens and discovery of novel bacteria - Mei-Na Li; Ting Wang; Nan Wang; Qiang Han; Xue-Ming You; Shuai Zhang; Cui-Cui Zhang; Yong-Qiang Shi; Pei-Zhuang Qiao; Cheng-Lian Man; Teng Feng; Yue-Yue Li; et al. (Antonie van Leeuwenhoek, 2024)

Seasonal variations and the prevalence of phenolic profiles in ambient fine particulate matter and their impact on oxidative potential - Lulu Wang; Minmin Wu; Bin Han; Mengyi Wang; Ruifang Li; Yang Shen; Zhijia Zhuang; Zhu Wang; Tao Jing (Journal of Hazardous Materials, 2024)

Mineralogy and geochemistry of the Cambrain Shuijingtuo Formation black shales from Western Hubei, China: implications on enrichment of critical metals and paleoenvironment - Yuan Wang; Jing Li; Yang Lin; Xinguo Zhuang; Vanlong Hoang; Peng Wu; Xin Luo; Han Zhang; Xiaoyang Zhang (Frontiers in Marine Science, 2024)
Black shales have attracted the attention of numerous researchers not only due to their high potential as hydrocarbon source rocks and shale gas reservoirs, but also to the enrichment of critical metal elements in black shale series. Black shale of the Cambrian Shuijingtuo Formation is one of the most important black shales in the Yangtze platform. This paper conducts integrated research on the mineralogical and geochemical characteristics of this black shale from the Luojiacun section in Western Hubei Region, aiming at elaborating the enrichment mechanism of elevated critical metal elements in the Shuijingtuo black shale. Minerals in the Shuijingtuo black shale are predominantly composed of quartz (avg. 43.0%) and clay minerals (avg. 32.5%), with small proportions of calcite, albite, clinochlore, and pyrite. The Shuijingtuo black shale is characterized by high total organic carbon (TOC, avg. 3.9%) content and enriched in V-Ni-Cr-U and Sr-Ba critical metal assemblages. The elevated V, Cr, Ni, and U present dominant organic affinities, while Sr and Ba are closely correlated to calcite and pyrite, respectively. The enrichment of V-Cr-Ni-U critical element assemblages in Shuijingtuo black shale are ascribed to the high primary productivity, anoxic depositional conditions, marine biologic production, and low-temperature hydrothermal activities. The enrichment of Sr and Ba is related to the high primary productivity and anoxic depositional conditions, respectively.

Water transfer projects and microplastics: Analyzing changes in lake environments with a focus on Wabu Lake, China - Bingyu Chen; Qian Wang; Zhimin Wang; Sanqing Han; Junjie Li; Xingmei Zhuang; Yuan Liu; Long Chen; Shuguang Zhu; Fazhi Xie (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Supersaturation- and external force-engineered high-quality 2D CsCu2I3 single-crystalline film for heterogeneous integration in photodetectors - Sancan Han; Xianyu Qiao; Yimin Li; Fei Wang; Dechao Yu; Jingcheng Xu; Songlin Zhuang; Xiaosheng Fang; Dawei Zhang (Chemical Engineering Journal, 2024)

Matrine inhibits invasion and migration of gallbladder cancer via regulating the PI3K/AKT signaling pathway - Rong-Liang Mo; Zhuang Li; Peng Zhang; Ming-Hui Sheng; Gen-Cheng Han; Deng-Qun Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Elevational distribution of forests and its spatiotemporal dynamics in subtropical China from 2000 to 2019 - Zhencan Zheng; Liuwen Zhuang; Guofang Miao; Han Liu; Zhiqiang Cheng; Wenyu Li; Rong Shang; Peng Gong; Jing Ming Chen (Science China Earth Sciences, 2024)

Evolutionary and functional analysis of metabotropic glutamate receptors in lampreys - Ruyu Zhuang; Zihao Yan; Yicheng Gao; Ayqeqan Nurmamat; Shuyuan Zhang; Min Xiu; Yuesi Zhou; Ya Pang; Ding Li; Liang Zhao; Xin Liu; Yinglun Han (Fish Physiology and Biochemistry, 2024)

Formation and growth of nanophase iron particles on the surface of Mercury revealed by experimental study - Ronghua Pang; Yang Li; Chen Li; Pengfei Zhang; Zhuang Guo; Sizhe Zhao; Han Yu; Li Wang; Chenxi Zhu; Shuangyu Wang; Kairui Tai; Qinwei Zhang; et al. (Acta Geochimica, 2024)

Prevalence of synthetic phenolic antioxidants in food contact materials from China and their implications for human dietary exposure through take-away food - Bin Han; Yinzhu Shang; Hui Wang; Yang Shen; Ruifang Li; Mengyi Wang; Zhijia Zhuang; Zhu Wang; Min Fang; Tao Jing (Journal of Hazardous Materials, 2024)

Risk performance analysis approach for convoy operations via a hybrid model of STPA and DBN: A case from ice-covered waters - Xiaoming Zhu; Shenping Hu; Zhuang Li; Jianjun Wu; Xue Yang; Shanshan Fu; Bing Han (Ocean Engineering, 2024)

Using ultrasonic-assisted sodium bicarbonate treatment to improve the gel and rheological properties of reduced-salt pork myofibrillar protein - Zhong-Wei Wu; Xue-Yan Shang; Qin Hou; Jing-Guo Xu; Zhuang-Li Kang; Han-Jun Ma (Meat Science, 2024)

Numerical simulation investigation on the seismic performance of high-strength concrete columns reinforced with PVA fibers and HTRB630 steel bars - Mei-Ling Zhuang; Chuanzhi Sun; Jinbo Chen; Hanbo Zhu; Li Gao; Yan Qiao; Yuefeng Shao; Weihua Zhang; Yixiang Han; Guangdong Bao (Bulletin of Earthquake Engineering, 2024)

Enhancing Growth and Intestinal Health in Triploid Rainbow Trout Fed a Low-Fish-Meal Diet through Supplementation with Clostridium butyricum - Chang’an Wang; Fangyuan Li; Di Wang; Shaoxia Lu; Shicheng Han; Wei Gu; Haibo Jiang; Zhuang Li; Hongbai Liu (Fishes, 2024)
This study evaluates the effects of dietary Clostridium butyricum on growth performance and intestinal health in triploid rainbow trout (Oncorhynchus mykiss). Administered in a 12-week trial, five isonitrogenous and isolipidic feeds contained different C. butyricum levels [G1 (0), G2 (1.6 × 106 CFU/g), G3 (1.2 × 107 CFU/g), G4 (1.1 × 108 CFU/g), and G5 (1.3 × 109 CFU/g)]. Significant enhancements in growth performance, including improved feed conversion ratios and specific growth rates in the G4 group, were indicative of enhanced nutrient utilization, corroborated by optimal digestive enzyme activity levels. Antioxidant capabilities were also enhanced in the G4 group, indicated by increased serum superoxide dismutase and catalase activities, along with a significant decrease in malondialdehyde levels. Gut microbiota analysis indicated a probiotic concentration-dependent modulation of microbial communities, with a marked enrichment in beneficial bacterial phyla like Firmicutes in the G4 group. This microbial shift correlated with significant downregulations in immune-related gene expressions, including interleukins (IL-1β, IL-8), NF-κB, MyD88, and TNF-α, highlighting an activated immune response. Correspondingly, serum lysozyme and immunoglobulin M contents were significantly elevated in the G4 group. Challenge tests with Aeromonas salmonicida exhibited the higher disease resistance of fish fed the G4 diet. In conclusion, the study shows the potential of dietary C. butyricum, especially at 1.1 × 108 CFU/g, in enhancing the growth, health, and disease resistance of triploid rainbow trout through modulating gut microflora and stimulating immune responses.

Transient anoxic conditions boost N2O emissions by stimulating denitrification capacity and decreasing N2O reduction ratio in soils with different carbon substrates - Shan Zhuang; Junjun Ding; Wei Lin; Qian Zheng; Xinyue Kou; Qiaozhen Li; Chunying Xu; Lili Mao; Yanshuo Pan; Ying Gao; Dongfei Han; Yuzhong Li (Soil Biology and Biochemistry, 2024)

Valorization of Nannochloropsis oceanica for integrated co-production of violaxanthin cycle carotenoids - Rui Yin; GengJie Zhuang; Yuhui Lei; Jichang Han; Yanrong Li; Jinrong Zhang; Xiaojun Yan (Bioresource Technology, 2024)

Establishment of a gill cell line from yellowfin seabream ( Acanthopagrus latus ) for studying Amyloodinium ocellatum infection of fish - Zhicheng Li; Jingyu Zhuang; Jiaming Chen; Jizhen Cao; Qing Han; Zhi Luo; Baotun Wang; Hebing Wang; Anxing Li (Journal of Fish Diseases, 2024)
Amyloodinium ocellatum is among the most devastating protozoan parasites, causing huge economic losses in the mariculture industry. However, the pathogenesis of amyloodiniosis remains unknown, hindering the development of targeted anti‐parasitic drugs. The A. ocellatum in vitro model is an indispensable tool for investigating the pathogenic mechanism of amyloodiniosis at the cellular and molecular levels. The present work developed a new cell line, ALG, from the gill of yellowfin seabream ( Acanthopagrus latus ). The cell line was routinely cultured at 28°C in Dulbecco's modified Eagle medium (DMEM) supplemented with 15% fetal bovine serum (FBS). ALG cells were adherent and exhibited an epithelioid morphology; the cells were stably passed over 30 generations and successfully cryopreserved. The cell line derived from A. latus was identified based on partial sequence amplification and sequencing of cytochrome B ( Cyt b ). The ALG was seeded onto transwell inserts and found to be a platform for in vitro infection of A. ocellatum , with a 37.23 ± 5.75% infection rate. Furthermore, scanning electron microscopy (SEM) revealed that A. ocellatum parasitizes cell monolayers via rhizoids. A. ocellatum infection increased the expression of apoptosis and inflammation‐related genes, including caspase 3 ( Casp 3 ), interleukin 1 ( IL‐1 ), interleukin 10 ( IL‐10 ), tumour necrosis factor‐alpha ( TNF‐α ), in vivo or in vitro. These results demonstrated that the in vitro gill cell monolayer successfully recapitulated in vivo A. latus host responses to A. ocellatum infection. The ALG cell line holds great promise as a valuable tool for investigating parasite–host interactions in vitro.

Spatial distribution and main drivers of soil selenium in Taihu Lake Basin, Southeast China - Han Zhang; Zhencheng Ouyang; Manchun Li; Boqing Wen; Sudan Zhuang; Xiaomin Zhao; Penghui Jiang (Journal of Hazardous Materials, 2024)

Maternal serum neonicotinoids during early-mid pregnancy and congenital heart diseases in offspring: An exploratory study - Yanji Qu; Adela Jing Li; Xiaoqing Liu; Shao Lin; Michael S. Bloom; Ximeng Wang; Xiaohong Li; Hui Wang; Fengzhen Han; Xiangmin Gao; Yong Wu; Kaiqin Huang; et al. (Environmental Pollution, 2024)

Galvanized material is a promising approach to control Amyloodinium ocellatum infection in fishes - Zhi Luo; Zhihong Zhong; Zhicheng Li; Jingyu Zhuang; Han Li; Baotun Wang; Jizhen Cao; Qing Han; Chenxi Wang; Anxing Li (Aquaculture, 2024)

Preparation of double-system imprinted polymer-coated multi-walled carbon nanotubes and their application in simultaneous determination of thyroid-disrupting chemicals in dust samples - Zhijia Zhuang; Danqi Cheng; Bin Han; Ruifang Li; Yang Shen; Mengyi Wang; Zhu Wang; Wenping Ding; Guang Chen; Yikai Zhou; Tao Jing (Science of The Total Environment, 2024)

Corrigendum to “Aluminum chloride induced splenic lymphocytes apoptosis through NF-kB inhibition” [Chemico-Biol. Interact. 257 (2016) 94–100] - Cuicui Zhuang; Hui Huo; Wanfa Fu; Wanyue Huang; Lulu Han; Miao Song; Yanfei Li (Chemico-Biological Interactions, 2024)

Combined metabolome and transcriptome analysis reveals a critical role of lignin biosynthesis and lignification in stem-like pneumatophore development of the mangrove Avicennia marina - Yu-Chen Zhang; Li-Han Zhuang; Jia-Jie Zhou; Shi-Wei Song; Jing Li; He-Zi Huang; Bing-Jie Chi; You-Hui Zhong; Jing-Wen Liu; Hai-Lei Zheng; Xue-Yi Zhu (Planta, 2024)

Corrigendum to “Cytoprotective effect of deferiprone against aluminum chloride-induced oxidative stress and apoptosis in lymphocytes” [Toxicol. Lett. 285 (2018) 132–138] - Cuicui Zhuang; Yue She; Haiyang Zhang; Miao Song; Yanfei Han; Yanfei Li; Yanzhu Zhu (Toxicology Letters, 2023)

Role of antenatal anxiety in the relationship between maternal exposure to nitrogen dioxide and small for gestational age: A birth cohort study - Qiannan Wei; Weiwei Lin; Hedi Zhang; Yuming Lai; Shuling Zhuang; Zhenyan Han; Qingqing Wang; Lijie Wang; Wenzhuo Li; Li Wen; Hongying Hou; Qiansheng Hu (Science of The Total Environment, 2023)

Epithelial lining inspired protective shield for prolonged endotracheal intubation - Baisong Zhao; Meng-Han Bai; Luxi Zhang; Qingning Wang; Yongying Pan; Yan-Pu Li; Rui Hong; Juxiang Gou; Dongjie Zhang; Yuwei Liu; Gan-Ji Zhong; Ka Li; et al. (Chemical Engineering Journal, 2023)

Predicting maize yield in Northeast China by a hybrid approach combining biophysical modelling and machine learning - Jianzheng Li; Ganqiong Li; Ligang Wang; Denghua Li; Hu Li; Chao Gao; Minghao Zhuang; Jiayu Zhuang; Han Zhou; Shiwei Xu; Zhengjiang Hu; Enli Wang (Field Crops Research, 2023)

Synergistic single-atom Ru and MOF-derived oxygen vacancy ZrO2-porous carbon to boost the efficiency for electrochemical nitrogen fixation - Zhiya Han; Senhe Huang; Boxu Feng; Jingshun Zhang; Sheng Han; Xiaodong Zhuang; Rongbin Li (Chemical Engineering Journal, 2023)

Imbalance of multiple neurotransmitter pathways leading to depression-like behavior and cognitive dysfunction in the triple transgenic mouse model of Alzheimer disease - Meng Zhang; Li-yuan Liu; Yong Xu; Wen-zhi Wang; Nian-zhuang Qiu; Fang-fang Zhang; Feng Zhang; Xiao-dan Wang; Wei Chen; Xiao-yan Xu; Yong-feng Gao; Mei-hua Chen; et al. (Metabolic Brain Disease, 2023)

Long-term detraining reverses the improvement of lifelong exercise on skeletal muscle ferroptosis and inflammation in aging rats: fiber-type dependence of the Keap1/Nrf2 pathway - Zhuang-Zhi Wang; Hai-Chen Xu; Huan-Xia Zhou; Chen-Kai Zhang; Bo-Ming Li; Jia-Han He; Pin-Shi Ni; Xiao-Ming Yu; Yun-Qing Liu; Fang-Hui Li (Biogerontology, 2023)

An experimental animal model of yellowfin seabream (Acanthopagrus latus) for Amyloodinium ocellatum infection - Zhicheng Li; Zhihong Zhong; Jingyu Zhuang; Zhi Luo; Qing Han; Jizhen Cao; Baotun Wang; Anxing Li (Aquaculture, 2023)

Effect of safflower oil and magnetic field-modified soy 11S globulin on rheological and emulsifying properties of oil-in-water emulsions - Zhuang-Li Kang; Jing-jie Xie; Zhong-liang Hu; Yan-ping Li; Han-Jun Ma (Food Hydrocolloids, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Inhibiting thioredoxin glutathione reductase is a promising approach to controlling Cryptocaryon irritans infection in fish - Zhihong Zhong; Han Li; Zhicheng Li; Jizhen Cao; Chenxi Wang; Zhi Luo; Baotun Wang; Jingyu Zhuang; Qing Han; Anxing Li (Veterinary Parasitology, 2023)

Chemical characterization and source attribution of organic pollutants in industrial wastewaters from a Chinese chemical industrial park - Yihua Huang; Yinong You; Manman Wu; Min Han; Jin Zhang; Wei Gao; Danping Xie; Hongzhan Chen; Hui Ou; Ninghui Song; Chunlei Cheng; Wen Zhuang; et al. (Environmental Research, 2023)

Correction: Forest gaps accelerate the degradation of cellulose and lignin in decaying logs in a subalpine forest - Zhuang Wang; Bo Tan; Wanqin Yang; Qin Wang; Chenhui Chang; Lifeng Wang; Han Li; Chengming You; Rui Cao; Yurui Jiang; Jörg Müller (European Journal of Forest Research, 2023)

Effects of pre-emulsified safflower oil with magnetic field modified soy 11S globulin on the gel, rheological, and sensory properties of reduced-animal fat pork batter - Zhuang-Li Kang; Jing-jie Xie; Yan-ping Li; Wan-jie Song; Han-Jun Ma (Meat Science, 2023)

Improving the sensitivity and selectivity of sulfonamides electrochemical detection with double-system imprinted polymers - Bin Han; Wenbin Li; Yang Shen; Ruifang Li; Mengyi Wang; Zhijia Zhuang; Yikai Zhou; Tao Jing (Science of The Total Environment, 2023)

Effects of anthropogenic aerosols and sea salt aerosols during a summer precipitation event in the Yangtze River Delta - Peipei Han; Shu Li; Kun Zhao; Tijian Wang; Min Xie; Bingliang Zhuang; Mengmeng Li; Chong Liu (Atmospheric Research, 2023)

Growth and physiological–biochemical characteristics of cucumber (Cucumis sativus L.) in the presence of different microplastics - Haoran Zhuang; Xiaoyi Liu; Han Ma; Ruijing Li; Bo Liu; Ziyu Lin; Zhenxia Li (Arabian Journal of Geosciences, 2023)

Forest gaps accelerate the degradation of cellulose and lignin in decaying logs in a subalpine forest - Zhuang Wang; Bo Tan; Wanqin Yang; Qin Wang; Chenhui Chang; Lifeng Wang; Han Li; Chengming You; Rui Cao; Yurui Jiang; Jörg Müller (European Journal of Forest Research, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Acute Toxicity of a Novel anti-fouling Material Additive DCOIT to Marine Chlorella sp - Jin-Chuang Ru; Xue-Li Zhao; Zhi-Han Cao; Cheng-Zhuang Chen; Ping Li; Zhi-Hua Li (Bulletin of Environmental Contamination and Toxicology, 2022)

Immunogenicity and protective efficacy of a DNA vaccine inducing optimal expression of the SARS-CoV-2 S gene in hACE2 mice - Zhuo-xin Li; Sheng Feng; He Zhang; Xin-yu Zhuang; Chao Shang; Shi-yu Sun; Ji-cheng Han; Yu-biao Xie; Jin-yong Zhang; Wei Wang; Cheng-hui Li; Guan-yu Zhao; et al. (Archives of Virology, 2022)

Double knock-in pig models with elements of binary Tet-On and phiC31 integrase systems for controllable and switchable gene expression - Qin Jin; Xiaoyu Yang; Shixue Gou; Xiaoyi Liu; Zhenpeng Zhuang; Yanhui Liang; Hui Shi; Jiayuan Huang; Han Wu; Yu Zhao; Zhen Ouyang; Quanjun Zhang; et al. (Science China Life Sciences, 2022)

Alterations in gut microbiota and metabolites associated with altitude-induced cardiac hypertrophy in rats during hypobaric hypoxia challenge - Zhiyuan Pan; Yichen Hu; Zongyu Huang; Ni Han; Yan Li; Xiaomei Zhuang; Jiye Yin; Hui Peng; Quansheng Gao; Wenpeng Zhang; Yong Huang; Yujun Cui; et al. (Science China Life Sciences, 2022)

SbbHLH85, a bHLH member, modulates resilience to salt stress by regulating root hair growth in sorghum - Yushuang Song; Simin Li; Yi Sui; Hongxiang Zheng; Guoliang Han; Xi Sun; Wenjing Yang; Hailian Wang; Kunyang Zhuang; Fanying Kong; Qingwei Meng; Na Sui (Theoretical and Applied Genetics, 2022)

Identification of nitrate sources in the Jing River using dual stable isotopes, Northwest China - Jing Hu; Mengyan Pan; Tianhao Han; Zhi Zhuang; Yunning Cao; Kaili Yang; Yuliang Li; Weiguo Liu (Environmental Science and Pollution Research, 2021)

Genome-wide characterization and analysis of the anthocyanin biosynthetic genes in Brassica oleracea - Fengqing Han; Xiaoli Zhang; Limei Yang; Mu Zhuang; Yangyong Zhang; Yumei Liu; Zhansheng Li; Yong Wang; Zhiyuan Fang; Jialei Ji; Honghao Lv (Planta, 2021)

Lipin1 Alleviates Autophagy Disorder in Sciatic Nerve and Improves Diabetic Peripheral Neuropathy - Meijian Wang; Min Xie; Shuyan Yu; Pan Shang; Cong Zhang; Xiaolin Han; Cuiqin Fan; Li Chen; Xianghua Zhuang; Shihong Chen (Molecular Neurobiology, 2021)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Resolvin D1 Attenuates Innate Immune Reactions in Experimental Subarachnoid Hemorrhage Rat Model - Guang-Jie Liu; Tao Tao; Xiang-Sheng Zhang; Yue Lu; Ling-Yun Wu; Yong-Yue Gao; Han Wang; Hai-Bin Dai; Yan Zhou; Zong Zhuang; Chun-Hua Hang; Wei Li (Molecular Neurobiology, 2021)

Application of comprehensive support techniques to roadway tunneling in vicinity of Ordovician carbonate confined aquifers under complicated tectonic conditions - Huiyong Yin; Cuiyue Zhao; Yutao Zhai; Shizhen Sang; Han Zhao; Shujing Li; Haisong Li; Weijie Zhang; Xuehou Zhuang (Carbonates and Evaporites, 2020)

Petrogenesis of post-collisional magmatism at the Carboniferous–Permian boundary in central Inner Mongolia, NE China: insights into when the Hegenshan Ocean closed? - Lu Lu; Yong Qin; Kai-Jun Zhang; Chun-Yuan Han; Zhuang-Fu Li; Tao Wei; Zheng-Hui Qu; Yong-Zhong Xu (International Geology Review, 2020)

Creation of fertility-restored materials for Ogura CMS in Brassica oleracea by introducing Rfo gene from Brassica napus via an allotriploid strategy - Hai-long Yu; Zhi-yuan Li; Wen-jing Ren; Feng-qing Han; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Yu-mei Liu; Zhi-yuan Fang; Yang-yong Zhang (Theoretical and Applied Genetics, 2020)
Key message Ogura CMS fertility-restored materials, with 18 chromosomes, normal seed setting, stable fertility and closer genetic background to the parent Chinese kale, were successfully developed in B. oleracea via a triploid strategy for the first time. Abstract Ogura cytoplasmic male sterility (CMS) is the most widely used sterile type in seed production for commercial hybrids of Brassica oleracea vegetables. However, the natural Ogura CMS restorer line has not been found in B. oleracea crops. In this study, the triploid strategy was used with the aim to create euploid B. oleracea progenies with the Rfo gene. The allotriploid AAC hybrid YL2 was used as a male parent to backcross with Ogura CMS Chinese kale. After successive backcrosses, the BC 2 Rfo -positive individual 16CMSF2-11 and its BC 3 progenies, with 18 chromosomes, were developed, which were morphologically identical to the parent Chinese kale. Compared with F 1 and BC 1 plants, it showed stable fertility performance, and regular meiosis behavior and could produce seeds normally under natural pollination. The genomic composition analysis of Rfo -positive progenies by using molecular markers showed that more than 87% of the C-genome components of BC 3 Rfo -progenies recovered to the parent Chinese kale, while most or all of the A n -genome segments were lost in 16CMSF2-11 and its progenies. The results suggested that the genetic background of Rfo -positive individuals was closer to that of the parent Chinese kale along with backcrossing. Hereof, the Ogura CMS fertility-restored materials of Chinese kale were successfully created via triploid strategy for the first time, providing a bridge for utilizing the Ogura CMS B. oleracea germplasm in the future. Moreover, our study indicates that the triploid strategy is effective for transferring genes from B. napus into B. oleracea .

Spatiotemporal distribution of anthropogenic aerosols in China around 2030 - Shu Li; Tijian Wang; Bingliang Zhuang; Min Xie; Yong Han (Theoretical and Applied Climatology, 2019)

Three Camellia sinensis glutathione S-transferases are involved in the storage of anthocyanins, flavonols, and proanthocyanidins - Yajun Liu; Han Jiang; Yue Zhao; Xin Li; Xinlong Dai; Juhua Zhuang; Mengqing Zhu; Xiaolan Jiang; Peiqiang Wang; Liping Gao; Tao Xia (Planta, 2019)

Fine mapping and candidate gene identification of the genic male-sterile gene ms3 in cabbage 51S - Fengqing Han; Kaiwen Yuan; Congcong Kong; Xiaoli Zhang; Limei Yang; Mu Zhuang; Yangyong Zhang; Zhansheng Li; Yong Wang; Zhiyuan Fang; Honghao Lv (Theoretical and Applied Genetics, 2018)

Histamine Excites Striatal Dopamine D1 and D2 Receptor-Expressing Neurons via Postsynaptic H1 and H2 Receptors - Qian-Xing Zhuang; Han-Ting Xu; Xu-Juan Lu; Bin Li; Wing-Ho Yung; Jian-Jun Wang; Jing-Ning Zhu (Molecular Neurobiology, 2018)

A comparison of amorphous calcium carbonate crystallization in aqueous solutions of MgCl2 and MgSO4: implications for paleo-ocean chemistry - Mei Han; Yanyang Zhao; Hui Zhao; Zuozhen Han; Huaxiao Yan; Bin Sun; Ruirui Meng; Dingxiang Zhuang; Dan Li; Binwei Liu (Mineralogy and Petrology, 2018)

Calcium carbonate precipitation by Synechocystis sp. PCC6803 at different Mg/Ca molar ratios under the laboratory condition - Zuozhen Han; Ruirui Meng; Huaxiao Yan; Hui Zhao; Mei Han; Yanyang Zhao; Bin Sun; Yanbiao Sun; Jie Wang; Dingxiang Zhuang; Wenjun Li; Lingxue Lu (Carbonates and Evaporites, 2017)

Modeling of urban heat island and its impacts on thermal circulations in the Beijing–Tianjin–Hebei region, China - Mengmeng Li; Tijian Wang; Min Xie; Bingliang Zhuang; Shu Li; Yong Han; Nianliang Cheng (Theoretical and Applied Climatology, 2017)

Morphological and molecular characterization of the second backcross progenies of Ogu-CMS Chinese kale and rapeseed - Hai-long Yu; Zhi-yuan Li; Li-mei Yang; Yu-mei Liu; Mu Zhuang; Lu-gang Zhang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Zhi-yuan Fang; Yang-yong Zhang (Euphytica, 2017)

Microsatellite records for volume 8, issue 4 - Alejandra Paola Ojeda; Alexandre Wagner Silva Hilsdorf; Ana Caroline Leite; Ao-ao Yang; Ayako Izuno; Chongbo He; Chun-ya Zhou; Daisuke Kyogoku; Danilo Caneppele; Dongmei Zhu; Fernando Stopato da Fonseca; Hao Yin; et al. (Conservation Genetics Resources, 2016)

Effects of Corticosterone on Immune Functions of Cultured Rat Splenic Lymphocytes Exposed to Aluminum Trichloride - Xu Yang; Feibo Xu; Cuicui Zhuang; Chongsheng Bai; Wanyue Huang; Miao Song; Yanfei Han; Yanfei Li (Biological Trace Element Research, 2016)

Development of a novel allele-specific Rfo marker and creation of Ogura CMS fertility-restored interspecific hybrids in Brassica oleracea - Hai-long Yu; Zhi-yuan Fang; Yu-mei Liu; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Yang-yong Zhang (Theoretical and Applied Genetics, 2016)

Cochliomycin A inhibits the larval settlement of Amphibalanus amphitrite by activating the NO/cGMP pathway - Kai-Ling Wang; Gen Zhang; Jin Sun; Ying Xu; Zhuang Han; Ling-Li Liu; Chang-Lun Shao; Qing-Ai Liu; Chang-Yun Wang; Pei-Yuan Qian (Biofouling, 2016)

Serum Iodine Is Increased in Subjects Having Budd–Chiari Syndrome - Yinping Zhuang; Maoheng Zu; Jingjing Li; Yong Wang; Cuiping Han; Qingqiao Zhang; Wei Xu; Ning Wei; Kai Xu (Biological Trace Element Research, 2015)

Low-Toxicity Diindol-3-ylmethanes as Potent Antifouling Compounds - Kai-Ling Wang; Ying Xu; Liang Lu; Yongxin Li; Zhuang Han; Jun Zhang; Chang-Lun Shao; Chang-Yun Wang; Pei-Yuan Qian (Marine Biotechnology, 2015)

Cloning and molecular characterization of a myosin light chain gene from Puccinia striiformis f. sp. tritici - Jie Liu; Li-Na Han; Qiong Zhang; Qiu-Ling Wang; Qing Chang; Hua Zhuang; Jia Liu; Man Li; Dan Yu; Zhen-Sheng Kang (World Journal of Microbiology and Biotechnology, 2014)

Halobellus rarus sp. nov., a halophilic archaeon from an inland salt lake of China - Wen-Jiao Zhang; Dong Han; Xing-Xing Qiu; Mei-Lin Zhao; Yun-Zhuang Mou; Heng-Lin Cui; Zheng-Rong Li (Antonie van Leeuwenhoek, 2013)

Eddy covariance tilt corrections over a coastal mountain area in South-east China: Significance for near-surface turbulence characteristics - Li Liu; Tijian Wang; Zhenhai Sun; Qingeng Wang; Bingliang Zhuang; Yong Han; Shu Li (Advances in Atmospheric Sciences, 2012)

Structural optimization and evaluation of butenolides as potent antifouling agents: modification of the side chain affects the biological activities of compounds - Yongxin Li; Fengying Zhang; Ying Xu; Kiyotaka Matsumura; Zhuang Han; Lingli Liu; Wenhan Lin; Yanxing Jia; Pei-Yuan Qian (Biofouling, 2012)

A new cytotoxic iridoid from Callicarpa nudiflora - Wen-Li Mei; Zhuang Han; Hai-Bin Cui; You-Xing Zhao; Yuan-Yuan Deng; Hao-Fu Dai (Natural Product Research, 2010)

Nuclear translocation of dihydrofolate reductase is not a pre-requisite for DNA damage induced apoptosis - Ting-Ting Yuan; Ying Huang; Ci-Xiang Zhou; Yun Yu; Li-Shun Wang; Han-Yi Zhuang; Guo-Qiang Chen (Apoptosis, 2009)

Indirect radiative forcing and climatic effect of the anthropogenic nitrate aerosol on regional climate of China - Shu Li; Tijian Wang; Bingliang Zhuang; Yong Han (Advances in Atmospheric Sciences, 2009)